The predication of AgNOR value in reflection of environmental pollution carcinogenesis - Thekra A. Al-Kashwan (Al-Qadisiyah Journal of Pure Science, 2018)
The value of Nuclear organization region(AgNOR) count and polymorphism in association with carcinogens has not been clearly explained yet. The aim of study was to assess the value of mAgNOR, pAgNOR and pleomorphic analysis in bladder cancer for prediction of possibility of war pollution carcinogens in the causation of increase rates of cancer in Iraq. A retrospective study was carried out on 100 TCC Iraqi patients classified into groups; A: include 50 cases diagnosed at 2005-2006 and B: 50 cases diagnosed at 2012-2013, and 30 cystitis as control group. After sliver staining paraffin's sections, mAgNOR and pAgNOR, and both pleomorphic and single dots were counted and analyzed. The result shown that total mean of mAgNOR and pAgNOR for A, B and C groups were 2.6, 3.4, 1.68 and 12.4, 22.5, 1.6 respectively, with significantly increase in B group in comparisons with others (p≤0.05). mAgNOR was significantly higher in low grades and stage of B group in comparison with A group (p≤0.05), while pAgNOR was observed more frequently in both low and high grade and stage in this group rather than the other patient group (p≤0.05). overall mean of AgNOR was not significantly increased in B group in comparison with others, but AgNOR pleomorphism was significantly larger in low grade and stage in B group than in another malignant group(A) (p≤0.05)., and significantly associated with high grade and stage of this group only (p≤0.05). mAgNOR and pAgNOR counts with along AgNOR pleomorphism can be useful markers of cellular kinetic to predict the effect of war pollution carcinogens. pAgNOR and AgNOR pleomorphism cellular proliferation markers have more predicative value in characterizing cell kinetic. Further large study will be needed to confirm these results.